2020
DOI: 10.1108/ejmbe-01-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the perception of performance appraisal practices on individual innovative behavior

Abstract: Purpose The purpose of this paper is to analyze the impact of employees’ perception of performance appraisal (PA) practices on innovative behavior (IB). The authors also propose to analyze consistency, a dimension of Human Resource Management (HRM) system strength, as a moderating variable in the aforementioned relationship. Design/methodology/approach A quantitative study was conducted, using a sample of 166 employees carrying out highly qualified, intensive knowledge jobs in four industrial companies in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 76 publications
0
12
0
3
Order By: Relevance
“…A recent systematic literature review by Bos-Nehles et al (2017) on studies looking at the HRM-IWB link found that training, reward, job demand, feedback and job security were significant for IWB. However, despite the attention that HRM practices have gained in respect to IWB, research on rewards and performance appraisal is still scant and inconsistent (Canet-Giner et al, 2020). Recent studies on HRM and IWB have indicated that rewards and performance appraisal produce mixed findings and are in fact rarely considered (Bos-Nehles et al, 2017;Seeck and Diehl, 2017).…”
Section: Hrm Practices and Iwbmentioning
confidence: 99%
“…A recent systematic literature review by Bos-Nehles et al (2017) on studies looking at the HRM-IWB link found that training, reward, job demand, feedback and job security were significant for IWB. However, despite the attention that HRM practices have gained in respect to IWB, research on rewards and performance appraisal is still scant and inconsistent (Canet-Giner et al, 2020). Recent studies on HRM and IWB have indicated that rewards and performance appraisal produce mixed findings and are in fact rarely considered (Bos-Nehles et al, 2017;Seeck and Diehl, 2017).…”
Section: Hrm Practices and Iwbmentioning
confidence: 99%
“…Pada pengujian hipotesis ke enam, Berdasarkan pada tabel di atas dapat dikatakan bahwa variable Penilaian Kinerja dapat disimpulkan bahwa data mendukung hipotesis yang berarti variable Penilaian Kinerja berpengaruh secara positif signifikan terhadap Perilaku Inovatif. Hal ini sejalan dengan penelitian sebelum nya bahwa penilaian kinerja memiliki pengaruh besar dalam mencapai perilaku inovatif dengan adanya praktik penilaian pekerjaan melalui pemberian penghargaan, promosi pekerjaan dan pelatihan dalam bekerja hal ini jika dikelola dengan baik dapat mendorong terjadinya perilaku inovatif pada karyawan (Canet-Giner et al 2020: Ismail & Rishani, 2018.…”
Section: Diskusiunclassified
“…However in recent decades, sometimes this growth is reduced or elevated; for example, around the world financial collapse of 2009, due to the economic/working stress among families, a significant down in the next year and then a new incrementation trend to the rearrangement which probably influenced the family lifestyle and role. It is likely that an economic crisis can also affect the family system, and family problems can interfere with job performance, but a global crisis can trigger family suffering (Repetti et al , 2002; Richter et al , 2010; Chelariu and Stump, 2011; Richter et al , 2015; Canet-Giner et al , 2020; Dong et al , 2020; Wang et al , 2020a, b). Research has also produced an assessment instrument to measure the intensity of this conflict (Kim et al , 2019).…”
Section: Database Descriptionmentioning
confidence: 99%